One-Part Alkali-Activated Binder Produced from Tungsten-Molybdenum (W-Mo) Tailings - Georgy Lazorenko; Yanshuai Wang; Alexandr Fedotov; Anton Kasprzhitskii (Eng)
This study explores the feasibility of preparing a one-part alkali-activated binder produced from tungsten-molybdenum (W-Mo) tailings with sodium metasilicate (SM). A series of alkali-activated mortar samples were prepared, and the effects of the water/binder (W/B) ratio and mixture proportion on mechanical properties were investigated. Additionally, the microstructure and composition of the alkali-activated W-Mo tailings were characterized by using a combination of scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy techniques. Optimal results were achieved with a W/B ratio of 0.35 and a formulation containing 20% by weight of SM. Under these conditions, the cured samples exhibited an unconfined compressive strength of 11.2 MPa and a bulk density of 1726 kg/m3 after 28 days. The findings show the potential to advance tungsten-molybdenum mine waste upcycling and contribute to the production of environmentally sustainable building materials.